PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT GLOBAL WELINDO BATAM - septiawan, Septiawan; Heryenzus, Heryenzus (SCIENTIA JOURNAL, 2021)
Today's company competition is increasingly competitive, this study aims to examine the extent of the role of discipline and motivation in improving employee performance. PT Global Welindo Batam is a company that has been established since 2014 and PT Global Welindo Batam is a distributor engaged in the Manufacturing Industry and marine industry. The sampling technique is saturated sampling, by taking the entire population of 107 respondents. The data technique used is the distribution of questionnaires and literature studies. The analytical method used is multiple regression which includes: validity test, reliability test, normality test, multicholine meaning test, heteroscedasticity test, determination test, partial test. The results showed that the discipline partially affected 3.405 > 1.983 of the t table, so that 0.00 was smaller than 0.05 alpha. While the partial effect of motivation is 8.368 > 1.983 from t table. Together with discipline and have a significant influence. of 106,188 > 3,080 from F table, then 0.00 is smaller than alpha 0.05. And the significance value of the simultaneous test. The results of the study on employee performance, performance, and the R2 test showed an effect of 81.9%. The results showed that discipline and motivation had a significant and significant effect